A product analysis-based study on the mechanism of inflammable gas explosion suppression. (March 2021) - Wang, Le; Gao, Jiancun; Zhou, Shangyong; Hu, Shoutao; Sun, Xu; Wang, Tao; Bernatik, Ales; Skrinsky, Jan
Abstract: To study the mechanism of the suppressing effect of Expanded Aluminium (EA) on the premixed gas explosion, premixed methane-air and propane-air gases were undergone explosion reaction in the presence of EA in a self-designed closed pipeline with the overpressures and the compositions, rates and sensitivities of products analyzed. The results showed that the 9.5% methane-air and 5% propane-air explosions produced peak pressures decreased by 79.3% and 65.6%, and residual methane and propane contents increased by 270% and 560% respectively than without EA. In addition, the results revealed that the explosions of propane in the presence of EA produced less methane and carbon oxides contents, but more ethylene and propylene contents. The simulation showed that H, O, and OH are the key factors affecting the rate of products. The product compositions, together with other parameters, suggested that EA decreased temperature, inhibited chain initiation and propagation reaction, but facilitated chain termination reaction by advancing and accelerating the gas phase and wall destruction reaction of radicals, especially collisions and concentration of key free radicals. This new research method based on the analysis of explosion products can be used for in-depth research into gas explosion features and shed light on the suppressing mechanism of EA in flammable gas explosion. Highlights: Filled Expanded aluminum (EA) increases reactants content after the explosion. EA reduced carbon monoxide and carbon dioxide production. EA inhibited chain initiation and propagation reactions. EA promoted chain termination reactions.